Structural characterization and surface activities of biogenic rhamnolipid surfactants from Pseudomonas aeruginosa isolate MN1 and synergistic effects against methicillin-resistant Staphylococcus aureus - Samadi, Nasrin; Abadian, Neda; Ahmadkhaniha, Reza; Amini, Farzaneh; Dalili, Dina; Rastkari, Noushin; Safaripour, Eliyeh; Mohseni, Farzaneh Aziz (Folia microbiologica, 2012)
The aim of present work was to study chemical structures and biological activities of rhamnolipid biosurfactants produced by Pseudomonas aeruginosa MN1 isolated from oil-contaminated soil. The results of liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis revealed that total rhamnolipids (RLs) contained 16 rhamnolipid homologues. Di-lipid RLs containing C(10)-C(10) moieties were by far the most predominant congeners among mono-rhamnose (53.29 %) and di-rhamnose (23.52 %) homologues. Mono-rhamnolipids form 68.35 % of the total congeners in the RLs. Two major fractions were revealed in the thin layer chromatogram of produced RLs which were then purified by column chromatography. The retardation factors (R (f)) of the two rhamnolipid purple spots were 0.71 for RL1 and 0.46 for RL2. LC-MS/MS analysis proved that RL1 was composed of mono-RLs and RL2 consisted of di-RLs. RL1 was more surface-active with the critical micelle concentration (CMC) value of 15 mg/L and the surface tension of 25 mN/m at CMC. The results of biological assay showed that RL1 is a more potent antibacterial agent than RL2. All methicillin-resistant Staphylococcus aureus (MRSA) strains were inhibited by RLs that were independent of their antibiotic susceptibility patterns. RLs remarkably enhanced the activity of oxacillin against MRSA strains and lowered the minimum inhibitory concentrations of oxacillin to the range of 3.12-6.25 μg/mL.
Keywords: Methicillin-Resistant Staphylococcus aureus; synergismus léků; Microbial Sensitivity Tests; Tandem Mass Spectrometry; Glycolipids; oxacilin; methicilin rezistentní Staphylococcus aureus; tandemová hmotnostní spektrometrie; půdní mikrobiologie; Chromatography, Thin Layer; chromatografie kapalinová; Drug Synergism; Anti-Bacterial Agents; Oxacillin; mikrobiální testy citlivosti; povrchově aktivní látky; chromatografie na tenké vrstvě; Chromatography, Liquid; Pseudomonas aeruginosa; Surface-Active Agents; antibakteriální látky; glykolipidy; Soil Microbiology